Determinants of Quit Behavior - Weiss, Andrew (Journal of Labor Economics, 1984)
Using a sample of newly hired semiskilled production workers at two manufacturing facilities, I investigate various factors affecting the probability of workers' quitting. Workers who quit a previous job to take the jobs studied are less likely to quit than are workers who were unemployed when they applied for the jobs surveyed. Workers assigned to more complex tasks are more likely to quit their jobs than are workers assigned to simpler tasks. Younger workers are more likely to quit than are older workers. Better-educated workers have lower quit propensities than do less well educated workers. These correlations, which stem from multiple regressions using probit estimation routines, can be explained by a model in which individuals' quit propensities are functions of their alternative opportunities, job satisfaction, and the pecuniary and nonpecuniary costs of quitting.